1995
DOI: 10.1136/jech.49.2.117
|View full text |Cite
|
Sign up to set email alerts
|

International variation in socioeconomic inequalities in self reported health.

Abstract: Study objective -To assess the extent to which the size of socioeconomic inequalities in self reported health varies among industrialised countries. Design -Cross sectional data on the association between educational level and several health indicators were obtained from national health interview surveys. This association was quantified by means of an inequality index based on logistic regression analysis. Setting -The national, non-institutionalised populations of the United Kingdom,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
0
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 17 publications
7
92
0
7
Order By: Relevance
“…More educated individuals are more likely to report illness because of their greater degree of self-awareness, and thus the effect of education on SPH can be underestimated. Our findings regarding the importance of education are consistent with previous research suggesting that education is a very reliable and stable predictor of health and mortality (Kunst, Geurts, and van den Berg 1995;Bobak et al 1998;Shkolnikov et al 1998;Bobak et al 2000;Perlman and Bobak 2008).…”
Section: Summary and Discussionsupporting
confidence: 82%
“…More educated individuals are more likely to report illness because of their greater degree of self-awareness, and thus the effect of education on SPH can be underestimated. Our findings regarding the importance of education are consistent with previous research suggesting that education is a very reliable and stable predictor of health and mortality (Kunst, Geurts, and van den Berg 1995;Bobak et al 1998;Shkolnikov et al 1998;Bobak et al 2000;Perlman and Bobak 2008).…”
Section: Summary and Discussionsupporting
confidence: 82%
“…A correlation study (Baquet et al, 1991), a cross-sectional study (Faivre et al, 1989) and a case-control study (Bidoli et al, 1992) reported no association between education and colon cancer risk for women, while an inverse association was found in a crosssectional study (Williams and Horm, 1977), and in two cohort studies in Scandinavia (Pukkala and Teppo, 1986;Vagero and Persson, 1986) significant positive associations were reported. We did not find an association between education and colon cancer, which is consistent with the finding that health differences between SES categories for women are Kunst et al, 1993), probably because of relatively small differences in education within the female population.…”
Section: Discussionsupporting
confidence: 81%
“…This has already been found in several other studies conducted in high income countries (HICs) [7,12,23,24] and we showed that this also the case in a number of middle and low-income countries (MLICs).…”
Section: Percentages In Less Good Health (Whshsi and Srh) By Age And supporting
confidence: 65%